Mating success and potential male-worker conflict in a male-dimorphic ant - Darrouzet Eric; Schrempf Alexandra; Heinze Jürgen (BMC Evolutionary Biology, 2007)
Abstract Background Males of many species adjust their reproductive tactics with regard to their condition and status. For example, large males may develop weapons and fight for access to females, whereas small or undernourished males do not express costly weapons or ornaments and sneak copulations. Different condition-dependent reproductive tactics may be associated with unequal average fitness, but the tactic chosen by a given male under given circumstances is thought to result in the highest possible fitness return. The ant species Cardiocondyla obscurior exhibits an environment-controlled polymorphism of docile, winged males and aggressive "ergatoid" males. Ergatoid males, which can replenish their sperm supply throughout their lives, engage in lethal fighting, and attempt to monopolize all female sexuals available in their nests, were previously assumed to gain higher lifetime reproductive success than the peaceful, winged males, which disperse to mate away from the nest and whose spermatogenesis is limited to the first days of adult life. However, precise data on male mating success have as yet not been available. Here, we compare the average mating success of the two male morphs, taking the high mortality rate of immature ergatoid males into account. Because individuals in insect societies may have opposing interests about their own development, we also investigate whether the interests of male larvae coincide with those of the workers and the rest of the society. Results When the survival probability of males is taken into account, winged males are more likely to mate multiply and in consequence have a higher estimated average mating success than ergatoid males. Therefore, male larvae are expected to prefer developing into winged instead of ergatoid adults. Conclusion Though male larvae can expect a higher average mating success when developing into winged males, most colonies produce only ergatoid males under standard conditions. This might point at a novel type of potential kin conflict within the social insect colony. Because workers in insect societies usually control male larval development, ergatoid male production under normal conditions probably reflects the optimal allocation strategy of workers to maximise their inclusive fitness.